Low-sodium sand-like aluminum hydroxide and method for preparing the same
By controlling the supersaturation and adding active seed crystals, the contradiction between sodium content and particle size in alumina products was resolved, achieving the preparation of low-sodium granular aluminum hydroxide with high decomposition rate and low sodium content, thus improving product quality and production efficiency.
Patent Information
- Application Number
- CN202311005503.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2026-03-17
- Estimated Expiration
- 2043-08-10
AI Technical Summary
Existing technologies struggle to effectively reduce sodium content while maintaining alumina particle size, making it difficult to resolve the contradiction between product quality and decomposition rate, thus affecting the performance of aluminum electrolysis and ceramic applications.
By adjusting the supersaturation, promoting the growth of the (001) and (100) planes of gibbsite, and combining the addition of active seed crystals, the seeding temperature and time are controlled to achieve the preparation of low-sodium granular aluminum hydroxide, ensuring the decomposition rate and product quality.
It achieves high decomposition rate (greater than 50%) and low sodium content (less than 0.15%), with good product morphology, easy industrialization, and enhances the competitiveness of alumina production.
Smart Images

Figure CN116969492B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alumina production technology, and in particular to a low-sodium granulated aluminum hydroxide and its preparation method. Background Technology
[0002] Sandy alumina is a raw material for modern aluminum electrolysis, possessing advantages such as good fluidity, low dust loss, low dust content, and large specific surface area. The median particle size d of the product is... 50 (or d) 0.5 The alumina is mainly distributed between 60 and 80 μm, with γ-Al₂O₃ as the dominant phase and α-Al₂O₃ less than 10%. Sandy aluminum hydroxide, obtained from the decomposition of sodium aluminate solution, is the basis for the production of sandy alumina. Sandy alumina is produced by seeding coarse-grained aluminum hydroxide from a supersaturated sodium aluminate solution (hereinafter referred to as seeding), followed by calcination (or roasting) at 950–1100 °C.
[0003] Na₂O is a major impurity in metallurgical-grade alumina. In wear-resistant products and ceramic applications, Na₂O content significantly affects the mechanical strength and conductivity of alumina products. During aluminum electrolysis, Na₂O reacts chemically with the electrolyte, requiring the addition of aluminum fluoride. High Na₂O content also leads to increased conductivity, reducing the electrical insulation properties of alumina ceramics and wear-resistant products, and consequently weakening their mechanical strength. Furthermore, the conversion rate of α-Al₂O₃ decreases, which may cause deformation and cracking in alumina ceramics and wear-resistant products. Therefore, reducing the Na₂O content in both metallurgical and non-metallurgical-grade alumina has been a hot research topic.
[0004] To reduce the Na2O content in alumina, without considering post-treatment methods such as grinding and washing, acid immersion, or calcination and washing of aluminum hydroxide or alumina, the primary goal is to reduce the Na2O content in the seed product, specifically Al(OH)3. Therefore, based on the Bayer process for seeding, researchers have proposed several methods to reduce the Na2O content in Al(OH)3.
[0005] (1) High temperature separation method: In the separation of supersaturated sodium aluminate solution, the temperature of the first tank is increased to above 80℃ (CN200910243355), and then the temperature is lowered for separation. The Na2O content in Al(OH)3 is less than 0.1%, but the decomposition rate is between 24% and 31%.
[0006] (2) High temperature and high caustic ratio method: Increase the caustic ratio of sodium aluminate solution, or seed at high temperature (CN202111290800, CN201810984755), and the Na2O content in Al(OH)3 can be reduced to below 0.25% under low decomposition rate.
[0007] (3) Seed pretreatment method: The seed crystals are finely ground (CN201811605253) and treated with ultrasound. The seed crystals are added to sodium aluminate solution for seeding. The initial seeding temperature is controlled at 60-70℃ to obtain ultrafine aluminum hydroxide (1-4μm). The Na2O content in Al(OH)3 is between 0.03-0.06%.
[0008] To reduce the Na2O content of alumina to less than 0.25%, Wei Yinghui (Light Metals, 2020, 8:21-23) suggested that measures such as increasing the initial decomposition temperature (72℃), extending the decomposition time, increasing the concentration of caustic alkali in the semen, increasing the solid content of decomposition, reducing the concentration of organic matter, strengthening washing, and controlling the particle size could be adopted, but the decomposition rate and product particle size were not considered.
[0009] In actual production, when the decomposition rate is greater than 50%, the product becomes more refined, and the Na2O content in aluminum hydroxide increases. Increasing the initial seeding temperature (>70℃) or the final seeding temperature (~60℃) can reduce the Na2O content in aluminum hydroxide, but it will lower the decomposition rate (<50%). Therefore, the seeding decomposition rate is generally controlled at ~50%, which can yield high-alkali granular aluminum hydroxide with a Na2O content of 0.17-0.30%.
[0010] In summary, conventional methods such as increasing the initial seeding temperature, increasing the caustic soda ratio, or raising the caustic soda concentration can reduce the Na2O content in the seed Al(OH)3, but this will decrease the decomposition rate. While refining the seed crystals can increase the decomposition rate, the product cannot meet the requirements for a granular finish. Therefore, the contradiction between Na2O content and product particle size and decomposition rate has not yet been effectively resolved, making it difficult to scale up existing low-alkali seeding technologies for alumina production. Summary of the Invention
[0011] This invention provides a low-sodium granulated aluminum hydroxide and its preparation method, the purpose of which is to solve the above-mentioned problems existing in the background art.
[0012] To achieve the above objectives, embodiments of the present invention provide a low-sodium granular aluminum hydroxide and its preparation method. The present invention achieves seed decomposition of low-sodium granular aluminum hydroxide through the synergistic effect of controlling supersaturation, enhancing the growth of the (001), (110), and (100) planes of gibbsite, and promoting the agglomeration of coarser particles. The method involves pretreatment of the seed crystals in a sodium aluminate solution; then, the seed crystals, along with the remaining seed crystals and refined sodium aluminate solution, are placed in the first seed decomposition tank, with active seed crystals added. The initial temperature of the seed crystals is controlled at 65–80°C, and the final temperature at 48–60°C. The seed decomposition rate is above 50% after 35–50 hours, yielding low-sodium granular aluminum hydroxide with less than 0.15% Na₂O. The preparation method of the present invention requires less investment, is easy to industrialize, and produces high-quality products with high decomposition rates, balancing product quality and decomposition rate, which is beneficial for improving the competitiveness of alumina production enterprises in my country.
[0013] An embodiment of the present invention provides a method for preparing low-sodium granular aluminum hydroxide, comprising the following steps:
[0014] S1: Transfer some of the seed crystals into a sodium aluminate solution bath for pretreatment to obtain seed crystal slurry;
[0015] S2: Pump the seed slurry, the remaining seed crystals, and sodium aluminate concentrate together into the seed separation tank;
[0016] S3: Control the temperature of the first and last cells of the seed decomposition process, and add active seeds during the middle stage of seed decomposition to carry out seed decomposition.
[0017] S4: After seeding, the sample is separated and washed to obtain low-sodium granular aluminum hydroxide, wherein Na2O < 0.15 wt.%.
[0018] Preferably, the seed crystal in step S1 is fine aluminum hydroxide after the first or second classification, and the main phase is gibbsite.
[0019] Preferably, the seed crystals in the seed slurry in step S1 account for more than 3% of the total seed crystals; the total seed crystals are 2.0 to 4.0 of the seed crystal coefficient, or the seed crystal content is 450 to 800 g / L.
[0020] Preferably, the pretreatment conditions in step S1 are: slow stirring at a temperature of 80–105°C for 30–120 min.
[0021] Preferably, the sodium aluminate semen composition in step S2 is 130–165 g / L Na2O. k 140~195g / LAl2O3, of which α k The value is 1.35–1.52, the silicon index is greater than 200, and the carbon-alkali (Na₂O) content is... c ) accounts for the total alkali (Na2O) T ) amount <10%, sodium sulfate (Na2O) s The concentration of sodium oxalate is less than 1.5 g / L, and the concentration of sodium acetate is 0.2–2.5 g / L.
[0022] Preferably, in step S2, the seed slurry is cooled using a tubular heat exchanger, a shell-and-tube heat exchanger, or a coil heat exchanger before being pumped into the seed separation tank. The cooling device can also be other non-plate heat exchangers.
[0023] Preferably, the active seed crystals in step S3 are prepared from a solution of aluminum sulfate, sodium bicarbonate, and sodium aluminate; or are made by grinding metallurgical-grade aluminum hydroxide, wherein the median particle size (d) of the ground metallurgical-grade aluminum hydroxide is... 50 The thickness ranges from 10 to 65 μm.
[0024] Preferably, the addition of active seed crystals in step S3 during the seeding process means that the amount of active seed crystals added is less than 20 g / L after 6 to 10 hours of seeding.
[0025] Preferably, in step S3, the temperature of the first seeding cell is 65-80°C, and the temperature of the last seeding cell is 48-60°C; the seed decomposition time is 35-50 hours.
[0026] More preferably, in step S3, the temperature of the first seeding tank is 65-80°C, and the temperature is maintained at 80°C for 0.5-2 hours, at 75°C for 3-5 hours, and at 70°C for 5-8 hours.
[0027] Based on a general inventive concept, embodiments of the present invention also provide low-sodium granular aluminum hydroxide prepared by the above-described preparation method.
[0028] In the study of the aluminate ion reaction precipitation and particle crystallization process in supersaturated sodium aluminate solution, the present invention discovered the following mechanism:
[0029] (1) At high temperatures, the Al(OH)4 in the sodium aluminate solution... - High concentration, while Na + Al(OH)4 - The concentration of polyaluminate ions will decrease.
[0030] (2) In the seeding of supersaturated sodium aluminate solution, Na in the initial stage of seeding + Al(OH)4 - Na preferentially reacts and precipitates on the (001) crystal plane of gibbsite. + Diffusion rate and Al(OH)4 - When the reaction precipitation rate and particle agglomeration rate are mismatched, the Na2O content in the aluminum hydroxide product increases significantly (see appendix). Figure 1 ).
[0031] (3) The aluminum hydroxide analyzed was mainly gibbsite phase. The particle size and crystal facets of gibbsite significantly affected the Na2O content in the product. The finer the particle size, the higher the Na2O content. The (001), (110), and (100) crystal faces of gibbsite had high sodium content (see attached image). Figure 1 In addition, the alkali content is high at nucleation sites and defects.
[0032] (4) The aggregation rate of particles in the seed solution is closely related to the supersaturation of the solution, the amount of seed crystals, and the number of fine particles. Particles with a particle size of -20 μm are preferred for aggregation. At the same time, coarser particles with a particle size of >20 μm can also aggregate.
[0033] (5) In high caustic ratio sodium aluminate solutions, due to the Na+ content in the sodium aluminate solution... + Al(OH)4 -Because of the low number of ion pairs and the low Na2O content in the seeded aluminum hydroxide, adding active seed crystals during the seeding process can improve the decomposition rate without increasing the Na2O content in the aluminum hydroxide.
[0034] (6) Fine aluminum hydroxide particles (<5μm) have high apparent solubility. The finer the particles, the higher the apparent solubility and the easier they are to dissolve.
[0035] (7) Sodium carbonate, sodium sulfate and sodium oxalate are easily adsorbed on the seed crystals, and the particle zeta potential is more negative. These impurities significantly inhibit seeding, prolong the seeding induction period, and increase the alkali content of the product.
[0036] (8) Some organic substances in sodium aluminate solution (such as sodium oxalate or sodium acetate) can induce the growth of gibbsite crystals, which is beneficial to reducing the alkali content in the product.
[0037] The above-described solution of the present invention has the following beneficial effects:
[0038] (1) The granular alumina prepared by the seed of the present invention has a low alkali content. In the process of preparing low-alkali granular alumina by seed, the alumina is calcined at a temperature above 950°C, which can meet the quality requirements of modern aluminum electrolysis for alumina and solve the contradiction between product particle size and decomposition rate.
[0039] (2) The method for preparing low-sodium granulated aluminum hydroxide of the present invention has a high decomposition rate. Unlike traditional decomposition processes that result in low decomposition rates due to low-alkali aluminum hydroxide, the decomposition rate of the present invention is greater than 50%, thus resolving the contradiction between decomposition rate, product particle size, and product alkali content.
[0040] (3) The method for preparing low-sodium granulated aluminum hydroxide of the present invention is low-investment and easy to implement. The main equipment required in the seeding process of the present invention is the same as that required in the traditional seeding process. There is no need to add a complex bypass process or invest in large main equipment, so it is easy to implement.
[0041] (4) The low-sodium granular aluminum hydroxide of the present invention has a good product morphology. The primary particle size is uniform and the crystal face is well developed; the agglomerated product has a regular morphology and the calcined alumina product has a good morphology; the product has high strength, which is beneficial to improving the efficiency of modern aluminum electrolysis.
[0042] (5) The method for preparing low-sodium granulated aluminum hydroxide of the present invention has high added value. Unlike traditional high-alkali metallurgical grade alumina, low-sodium aluminum hydroxide or alumina can be used to prepare high-value-added fine alumina. Attached Figure Description
[0043] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0044] Figure 1 This is a schematic diagram of the gibbsite crystal plane in Embodiment 1 of the present invention;
[0045] Figure 2 This is a scanning electron microscope image of conventional granulated aluminum hydroxide, as shown in Comparative Example 1 of this invention.
[0046] Figure 3 This is a scanning electron microscope image of granulated aluminum hydroxide from Example 1 of the present invention;
[0047] Figure 4 This is a particle size distribution diagram of Al(OH)3 seed crystals after two seed cycles according to the present invention. Detailed Implementation
[0048] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.
[0049] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0050] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0051] Unless otherwise specified, the percentage sign "%" in this invention refers to the mass percentage; however, the percentage of a solution, unless otherwise specified, refers to the number of grams of solute contained in 100 mL of solution; the caustic ratio refers to the ratio of alkali (calculated as Na2O) to aluminum oxide molecules in the solution.
[0052] When referring to the particle size of aluminum hydroxide in this invention, the unit of particle size is "μm"; d50, unless otherwise specified, refers to the median diameter.
[0053] The weight parts mentioned in this invention can be weight units known in the art such as μg, mg, g, kg, or multiples thereof, such as 1 / 10, 1 / 100, 10 times, 100 times, etc.
[0054] This invention addresses existing problems by providing a low-sodium granulated aluminum hydroxide and its preparation method.
[0055] Example 1
[0056] A method for preparing low-sodium granulated aluminum hydroxide includes the following steps:
[0057] S1. Seed crystals (d) obtained from a single cyclone fractionation are mixed at a ratio of 100 g / L. 50 Add sodium aluminate solution (60.92 μm) and pretreat at 100 rpm; 1 L of sodium aluminate concentrate has the composition of Na2O. k 160.12g / L, Al2O3187.78g / L, α k 1.40, silicon index is 290, carbon-alkali (Na2O) c ) accounts for the total alkali (Na2O) T The concentration was 6.5%, with Na2C2O4 and CH3COONa at 0.2 g / L. Pretreatment was performed at 95 °C for 10 min.
[0058] S2. After the seed slurry is cooled by a tubular heat exchanger, it is mixed with 500g of seed crystals obtained from the first cyclone classification. The mixed slurry is then seeded.
[0059] S3. The initial temperature is 62℃, the final temperature is 50℃, and the seeding time is 45 hours. The seeding cooling regime is as follows: during the first 10 hours of seeding, the temperature is reduced at a rate of 0.40℃ / h, and during the later stages of seeding, the temperature is reduced at a rate of 0.23℃ / h. Simultaneously, 10 g / L d50 35.67μm of ball-milled active seed crystals are added at approximately 59℃ after 6 hours of seeding.
[0060] S4. After seeding, the decomposition rate was 50.3%. After vacuum filtration of the seeded slurry, washing with boiling water and drying, aluminum hydroxide was found to be in the gibbsite phase (see schematic diagram of crystal planes, as shown). Figure 1 (as shown), d 50 It is 73.02 μm, d 50 The particle size is 71.53 μm, the (001) facet area is small, the crystal faces are well-developed and regular, and there are few fine particles in the agglomerates (attachment). Figure 2 The Na₂O content in the product Al(OH)₃ is 0.14%.
[0061] Example 2
[0062] A method for preparing low-sodium granulated aluminum hydroxide includes the following steps:
[0063] S1, fine seed crystals (d) obtained from two cyclone fractionation processes are mixed at a ratio of 30 g / L. 50 A sodium aluminate solution (48.92 μm) was added for pretreatment at 50 rpm; the sodium aluminate solution had the composition of Na₂O. k 70.78 g / L, Al2O3 83.17 g / L, α k 1.40. Pre-treat at 100℃ for 100 min.
[0064] S2. After the seed crystal slurry is cooled by a tubular heat exchanger, it is mixed with 650g of seed crystals obtained from cyclone fractionation. This mixture is then mixed with sodium aluminate concentrate for seeding. The sodium aluminate concentrate has the composition Na₂O. k 160.12g / L, Al2O3187.78g / L, α k 1.40, silicon index is 250, carbon-alkali (Na2O) c ) accounts for the total alkali (Na2O) T The concentration was 7.5%, with Na2C2O4 and CH3COONa at 2.5 g / L.
[0065] S3. The initial temperature was 70℃, the final temperature was 55℃, and the seeding time was 45 hours. The seeding cooling regime was as follows: for the first 10 hours of seeding, the temperature was reduced at a rate of 0.90℃ / h, and for the later stages of seeding, the temperature was reduced at a rate of 0.18℃ / h. 5 g / L of active seed crystals (d50 12.04 μm) prepared by sodium bicarbonate initiation were added when the temperature reached approximately 62℃ after 8 hours of seeding.
[0066] S4. After seeding, the decomposition rate was 51.7%; after vacuum filtration, washing with boiling water, and drying, the aluminum hydroxide was in the gibbsite phase. 50 The particle size is 76.77 μm, and the Na2O content in the product Al(OH)3 is 0.12%.
[0067] Example 3
[0068] A method for preparing low-sodium granulated aluminum hydroxide includes the following steps:
[0069] S1. Add the primary vortex-fractionated seed crystals (d) at a ratio of 400 g / L. 50 (54.04 μm) was added to sodium aluminate solution and pretreated at 100 rpm; 1 L of semen composition was Na2O k 160.12g / L, Al2O3187.78g / L, α k 1.40, silicon index is 270, carbon-alkali (Na2O) c ) accounts for the total alkali (Na2O) T The concentration was 5.0%, and the concentration of Na2C2O4 was 0.5 g / L. Pretreatment was performed at 95℃ for 10 min.
[0070] S2. After the seed slurry is cooled by a tubular heat exchanger, it is mixed with 100g of seed crystals obtained from the first cyclone classification. The mixed slurry is then seeded.
[0071] S3. Initial temperature: 75℃; final temperature: 45℃; seeding time: 48 hours. The seeding cooling regime is as follows: During the initial 10 hours of seeding, cool at 1.50℃ / h to 60℃; during the middle 15 hours of seeding, cool at 0.67℃ / h to 50℃; during the later stages of seeding, cool at 0.22℃ / h. No active seed crystals are added during the middle stage of seeding.
[0072] S4. After the seeding process, the decomposition rate was 50.04%; after vacuum filtration, washing with boiling water, and drying, the aluminum hydroxide was in the gibbsite phase. 50 The particle size is 70.25 μm, and the Na2O content in the product Al(OH)3 is 0.11%.
[0073] Example 4
[0074] A method for preparing low-sodium granulated aluminum hydroxide includes the following steps:
[0075] S1. Seed crystals were obtained by secondary cyclone fractionation at a ratio of 50 g / L (d 50 A sodium aluminate solution (23.07 μm) was added for pretreatment at 60 rpm; the sodium aluminate solution had the composition of Na₂O. k 65.47 g / L, Al2O3 72.34 g / L, α k 1.49. Pre-treat at 105℃ for 10 min.
[0076] S2, after the seed crystal slurry is cooled by a tubular heat exchanger, it is mixed with 400g of seed crystals and concentrate (Na2O). k 140.92g / L, Al2O3167.98g / L, α k 1.38, silicon index is 270, carbon-alkali (Na2O) c ) accounts for the total alkali (Na2O) T The mixture contains 5% Na2O4 (1.7 g / L) and 0.9 g / L Na2C2O4. The mixed slurry is then used for seeding in the first seeding tank.
[0077] S3. The initial temperature was 75℃, the final temperature was 58℃, and the seeding time was 35 hours. The seeding cooling regime was as follows: cooling at 1.5℃ / h for the first 6 hours of seeding, and cooling at 0.28℃ / h for the later stages of seeding. 5 g / L of active seed crystals (d50 10.92 μm) prepared by aluminum sulfate initiation were added when the temperature reached approximately 63℃ after 8 hours of seeding.
[0078] S4. After the seeding process, the decomposition rate was 50.2%; after vacuum filtration, washing with boiling water, and drying, the aluminum hydroxide was in the gibbsite phase. 50 The particle size is 76.69 μm, and the Na2O content in the product Al(OH)3 is 0.09%.
[0079] Example 5
[0080] A method for preparing low-sodium granulated aluminum hydroxide includes the following steps:
[0081] S1. Seed crystals (d) obtained from a single cyclone fractionation are mixed at a ratio of 200 g / L. 50 (49.07 μm) was added to sodium aluminate solution and pretreated at 100 rpm; 1 L of semen composition was Na2O k 140.92g / L, Al2O3167.98g / L, α k 1.38, silicon index is 260, carbon-alkali (Na2O) c ) accounts for the total alkali (Na2O) T The concentration of Na₂O₅ was 10.0%; Na₂O₅ was 1.7 g / L, and Na₂C₂O₄ and CH₃COONa were 1.9 g / L. Pretreatment was carried out at 95 °C for 40 min.
[0082] S2. After the seed slurry is cooled by a tubular heat exchanger, it is mixed with 300g of seed crystals. The mixed slurry is then seeded.
[0083] S3. Initial temperature: 80℃; final temperature: 58℃; seeding time: 35 hours. The cooling rate during the seeding process was 2.0℃ / h for the first 3 hours and 0.50℃ / h for the later stages. 20 g / L of finely ball-milled active seed crystals (d50 23.18 μm) were added when the temperature reached approximately 70℃ after 6 hours of seeding.
[0084] S4. After the seeding process, the decomposition rate was 51.9%. After vacuum filtration, washing with boiling water, and drying, the aluminum hydroxide was found to be in the gibbsite phase with a d50 of 75.87 μm. The Na2O content in the product Al(OH)3 was 0.08%.
[0085] Figure 4 This is a particle size distribution diagram of Al(OH)3 seed crystals after two seed cycles according to the present invention.
[0086] Comparative Example 1
[0087] A method for separating granulated aluminum hydroxide seeds includes the following steps:
[0088] Aluminum hydroxide seed crystals (d) from a single cyclone fractionation were added at a ratio of 600 g / L. 50 When a sample with a viscosity of 62.92 μm is added to a sodium aluminate solution, the composition of 1 L of semen is Na₂O. k 160.12g / L, Al2O3187.78g / L, α k 1.40, silicon index greater than 270, carbon-alkali (Na2O) c ) accounts for the total alkali (Na2O) TThe amount was 10.0%. After mixing, the slurry was added to the seeding tank. The initial temperature was 62℃, the final temperature was 50℃, and the seeding time was 45 hours. The seed slurry was cooled before seeding. The seeding cooling regime was as follows: cooling at 0.40℃ / h for the first 10 hours of seeding, and cooling at 0.23℃ / h for the later stages of seeding. After seeding, the decomposition rate was 50.1%; after vacuum filtration, washing with boiling water, and drying, the aluminum hydroxide was in the gibbsite phase. 50 The particle size is 71.53 μm, the (001) surface area is large, the agglomerates contain many fine particles, and the crystal planes are poorly developed (attachment). Figure 3 The product Al(OH)3 contains 0.22% Na2O, and the calcined alumina contains 0.34% Na2O.
[0089] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for producing low-sodium, sand-like aluminum hydroxide, characterized by, The method comprises the following steps: S1: transferring part of the seed crystals into a sodium aluminate solution tank for pretreatment, wherein the pretreatment conditions are: slowly stirring at a temperature of 80-105℃ for 30-120 min to obtain a seed crystal slurry; the seed crystals are fine aluminum hydroxide after the first or second classification, and the main phase is gibbsite; S2: the seed slurry and the remaining seed, sodium aluminate concentrate are pumped into the decomposition first tank; the sodium aluminate concentrate has a composition of 130-165 g / L Na2O k , 140-195 g / L Al2O3, wherein, α k =1.35-1.52, the silicon amount index is greater than 200, the sodium carbonate accounts for <10% of the total alkali amount, the sodium sulfate concentration is less than 1.5 g / L, and the sodium oxalate and sodium acetate concentrations are 0.2-2.5 g / L; S3: controlling the temperature of the seed crystal decomposition first tank and the last tank, and adding active seed crystals in the seed crystal decomposition middle stage, wherein the active seed crystals are added in an amount of less than 20 g / L after 6-10 h of seed crystal decomposition; the active seed crystals are prepared from aluminum sulfate, sodium bicarbonate and sodium aluminate solution, or are prepared by grinding metallurgical grade aluminum hydroxide, wherein the median particle size of the ground metallurgical grade aluminum hydroxide is 10-65 μm; S4: after seed crystal decomposition, separating and washing to obtain low-sodium sandy aluminum hydroxide, wherein Na2O < 0.15 wt. %.
2. The process for producing low-sodium, sandy aluminum hydroxide according to claim 1, characterized by, In step S1, the amount of the seed crystals in the seed crystal slurry is more than 3% of the total amount of the seed crystals, wherein the total amount of the seed crystals is 2.0-4.0 times the seed crystal coefficient, or the seed crystal content is 450-800 g / L.
3. The method of producing low-sodium, sand-like aluminum hydroxide according to claim 1, characterized by, In step S2, the seed crystal slurry is cooled by a tube heat exchanger before being pumped into the seed crystal decomposition first tank.
4. The process for producing low-sodium, sand-like aluminum hydroxide according to claim 1, characterized by, In step S3, the temperature of the seed crystal decomposition first tank is 65-80℃, and the temperature of the last tank is 48-60℃; the seed crystal decomposition time is 35-50 h.
5. Low-sodium sandy aluminum hydroxide prepared by the preparation method of any one of claims 1-4.
Citation Information
Patent Citations
Method for preparing low-sodium aluminum hydroxide by decomposing sodium aluminate solution
CN101746796A
A low-sodium alumina decomposition process and low-sodium alumina
CN108751242B
Method for preparing high-temperature resistant low-sodium aluminum hydroxide powder
CN109368674A
Ultralow-sodium aluminum hydroxide and preparation method thereof
CN113788488A
Method of cooperatively regulating and improving crystal seed decomposition of sodium aluminate solution
CN108585007A